Persistent clavicle swelling in the infant - Maciel,Juliana (2019)
Introduction: Congenital pseudarthrosis of the clavicle is a rare entity of unknown etiology. It is more common in girls and on the right side. Diagnosis is challenging and often performed after the neonatal period, triggered by persistence of a clavicular prominence initially attributed to traumatic birth fracture. Case Report: Herein is presented the case of a healthy ten-month-old girl with a right clavicle prominence since neonatal period initially attributed to traumatic birth fracture. Radiographic examination of the clavicle revealed congenital pseudarthrosis of the right clavicle. Comments: One of the most common causes of clavicle swelling in the neonatal period is clavicle fracture due to birth trauma. Clavicular prominence persistence beyond four to six months should raise suspicion of this clinical entity.